PW 2007 Quad-bike related aeromedical retrievals in queensland 2010–2014. (November 2018) - Franklin, Richard C; King, Jemma C; Aitken, Peter; Elcock, Mark; Gibbs, Clinton; Leggat, Peter
Abstract : Background: Quad-bikes are commonly used for agricultural and recreational purposes in rural and remote locations and are a leading cause of unintentional deaths on farms. Of the 81 quad-bike related deaths that occurred in Australia between 2010 and 2014, 26 (32%) occurred in Queensland. Aims: Review of Queensland aeromedical data from 2010 to 2014 to explore the rate of quad-bike related aeromedical retrievals (hereafter termed retrievals only). Methods: Narrative text analysis of clinical information in the retrievals dataset to locate quad-bike related retrieval cases (hereafter cases) using search terms – All Terrain Vehicles (ATV), quad and 4-wheel. All cases confirmed to involve quad-bikes entered into a SPSS dataset. Appropriate data custodian, Public Health Act and ethics approval was obtained for use of data. Results: Of the 93 185 retrievals undertaken between 2010 and 2014, 11 576 were trauma-related (12.4%) and 277 (0.3%) were quad-bike related. Males (79.3%) and those of working age (19–39 and 40–65 years, 33.2% and 29.6% respectively) were the most common patient groups requiring quad-bike related retrievals. Cases were retrieved from outer regional (41.8%), very remote (25.3%), inner regional (17.2%) and remote (13.2%) localities. Half of all retrievals were retrieved by fixed wing (52.7%), and primary retrievals (50.2%). Information regarding helmet use was included in the clinical description in 35 (13%) cases. Roll-overs and falls were the main mechanisms listed when tasking quad-bike related aeromedical retrievals. Discussion and conclusions: Quad-bike related retrievals are being undertaken in Queensland, yet represent a small proportion of all quad-bike cases seen by medical professionals. The data lacks fidelity regarding the situation that precedes the need for aeromedical retrieval; however the use of existing quad-bike trauma and riding injury prevention stratagems are warranted, including use of helmets, rider age restrictions, crush protection devices and communicating with others regarding destination.